Direct synthesis of highly stretchable ceramic nanofibrous aerogels via 3D reaction electrospinning - Xiaota Cheng; Yi-Tao Liu; Yang Si; Jianyong Yu; Bin Ding (Nature Communications, 2022)
Ceramic aerogels are generally brittle and often tend to structurally collapse under large external tensile strain. Here the authors synthesize large-scale stretchable ceramic aerogels with interwoven crimped nanofibers by combining electrohydrodynamic method and 3D reaction electrospinning.